빵용 밀 품종의 등숙기 질소 시비 시기와 양이 글루텐 분획 및 빵 부피에 미치는 영향 - 조성우; Seong-woo Cho; 강택규; Taek-gyu Kang; 박철수; Chul Soo Park; 손재한; Jae-han Son; 최창현; Chang-hyun Choi; 정영근; Young-keun Cheong; et al. (Korean journal of crop science, 2018)
The purpose of this study was to evaluate the effects of nitrogen fertilization amount and timing of application on protein content, dough properties, change in protein fraction, and bread loaf volume for Korean wheat cultivars, Baekkang, Joongmo2008, and Saekeumkang, for bread with a superior gluten composition during the grain filling stage. Protein content increased with an increase in the amount of N and timing of application. The SDS segmentation volume (SDSS) increased with an increase in N, but there was no effect of the timing of N application on SDSS. An increase in N amount and timing of application caused a difference in dough properties, such as water absorption, mixing time, and tolerance, among the cultivars. Soluble and insoluble polymeric and monomeric protein contents increased with an increase in N amount and timing of application the three Korean wheat cultivars. The effects of N amount and application timing on bread loaf volume (BLV) varied among the cultivars. The BLV of Saekeumkang increased regardless of the N amount and timing of application, but that of Baekkang and Joongmo2008 cultivars was reduced. However, there was a positive correlation between protein content with the addition of N fertilization and BLV. In addition, SDSS, mixing time, and protein fractions were positively correlated with BLV. Since the response of fertilizer conditions was different for each wheat cultivar, it is necessary to build a suitable fertilizing system for each of them. Additionally, since the environment is changing, such as abnormal climate during the maturing period, research is needed to establish appropriate fertilizer conditions for varieties of bread wheat.